MicroRNA-92b targets tumor suppressor gene FBXW7 in glioblastoma - Grafals-Ruiz, Nilmary; Sánchez-Álvarez, Annelis O.; Santana-Rivera, Yasmarie; Lozada-Delgado, Eunice L.; Rabelo-Fernandez, Robert J.; Rios-Vicil, Christian I.; Valiyeva, Fatima; Vivas-Mejia, Pablo E. (Frontiers in Oncology, 2023)
Introduction Glioblastoma (GBM) is a highly aggressive and lethal primary brain tumor. Despite limited treatment options, the overall survival of GBM patients has shown minimal improvement over the past two decades. Factors such as delayed cancer diagnosis, tumor heterogeneity, cancer stem cell survival, infiltrative nature of GBM cells, metabolic reprogramming, and development of therapy resistance contribute to treatment failure. To address these challenges, multitargeted therapies are urgently needed for improved GBM treatment outcomes. MicroRNAs (miRNAs) are small non-coding RNAs that regulate gene expression. Dysregulated miRNAs have been identified in GBM, playing roles in tumor initiation, progression, and maintenance. Among these miRNAs, miR-92b (miRNA-92b-3p) has been found to be overexpressed in various cancers, including GBM. However, the specific target genes of miR-92b and its therapeutic potential in GBM remain poorly explored. Methods Samples encompassed T98G, U87, and A172 human GBM cell lines, GBM tumors from Puerto Rican patients, and murine tumors. In-situ hybridization (ISH) assessed miR-92b expression in patient tumors. Transient and stable transfections modified miR-92b levels in GBM cell lines. Real-time PCR gauged gene expressions. Caspase 3 and Trypan Blue assays evaluated apoptosis and viability. Bioinformatics tools (TargetScanHuman 8.0, miRDB, Diana tools, miRWalk) predicted targets. Luciferase assays and Western Blots validated miRNA-target interactions. A subcutaneous GBM Xenograft mouse model received intraperitoneal NC-OMIs or miR92b-OMIs encapsulated in liposomes, three-times per week for two weeks. Analysis utilized GraphPad Prism 8; statistical significance was assessed using 2-tailed, unpaired Student’s t-test and two-way ANOVA as required. Results This study investigated the expression of miR-92b in GBM tumors compared to normal brain tissue samples, revealing a significant upregulation. Inhibition of miR-92b using oligonucleotide microRNA inhibitors (OMIs) suppressed GBM cell growth, migration, and induced apoptosis, while ectopic expression of miR-92b yielded opposite effects. Systemic administration of liposomal-miR92b-OMIs in GBM xenograft mice resulted in reductions in tumor volume and weight. Subsequent experiments identified F-Box and WD Repeat Domain Containing 7 (FBXW7) as a direct target gene of miR-92b in GBM cells. Discussion FBXW7 acts as a tumor suppressor gene in various cancer types, and analysis of patient data demonstrated that GBM patients with higher FBXW7 mRNA levels had significantly better overall survival compared to those with lower levels. Taken together, our findings suggest that the dysregulated expression of miR-92b in GBM contributes to tumor progression by targeting FBXW7. These results highlight the potential of miR-92b as a therapeutic target for GBM. Further exploration and development of miR-92b-targeted therapies may offer a novel approach to improve treatment outcomes in GBM patients.